A new dawn in internal medicine education curriculum—a project by the residents, with the residents, for the residents. Issue 6 (2nd November 2022) - Latif, Azka; Ahsan, Muhammad Junaid; Jaffri, Abbis; Kapoor, Vikas; Tran, Amy; DeVrieze, Bradley; Nahas, Joseph; Kim, Michael; Porter, Joann; Mirza, Mohsin
Abstract: The academic half-day (AHD) curriculum is an alternative to the noon conference (NC) approach. To date, there is little literature evaluating the transition from NC to AHD in internal medicine residency programs. We investigated the effectiveness of AHD by comparing in-training exam (ITE) and American Board of Internal Medicine (ABIM) certifying exam scores of residents before and after implementation of AHD. In 2019, we transitioned to the AHD curriculum. Averages of three consecutive years of NC (2016–2018) and AHD (2019–2021) were used for statistical testing to determine ITE and ABIM score changes. The class of 2018 experienced both approaches. Cohen's d effect sizes were calculated to assess the magnitude of change in ITE and ABIM scores between NC (2016–2018) and AHD (2019–2021) cohorts. Residents' performance significantly improved ( P  < 0.05) on ABIM scores (513.80 ± 48.34) on average from 2019 to 2021 compared to ABIM scores (452.42 ± 49.72) on average from 2016 to 2018 with a large effect size of 1.27. Similarly, a significant ( P  = 0.005) improvement in ITE scores was observed from 2019 to 2021 with implementation of AHD compared to preceding NC scores (2016–2018) with a moderate effect size of 0.52. Participating residents in AHD sessions had higher ITE and ABIM scores compared to those in hourly NC didactic sessions with significantly improved resident attendance and overall satisfaction.